Dimorphandra mollis: an alternative as a source of flavonoids with antioxidant action - Hubinger, Silviane Z. [UNESP]; Cefali, Leticia C. [UNESP]; Vellosa, Jose C. R. [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Isaac, Vera Lucia Borges [UNESP]; Moreira, Raquel Regina Duarte [UNESP] (Colegio Farmaceuticos Provincia de Buenos Aires, 2010)
Dimorphandra mollis: An Alternative as a Source of Flavonoids with Antioxidant Action. Dimorphandra molls fruits are rich in flavonoids rutin and quercetin, which are compounds with high antioxidant activity and can be used to prevent diseases caused by free radicals. The aim of this study was to obtain an extract rich in flavonoids from fruits of D. mollis. The extract was analyzed using the methods of determination by spectrophotometry and high performance liquid chromatography. The presence of rutin and quercetin was identified in the extract, which showed a total flavonoids content of 33.71 To. The extract also showed antioxidant activity as scanvanger of DPPH and ABTS radicals. It was possible to conclude that D. mollis fruits are a rich source of flavonoids with antioxidant action.
Keywords: Antioxidant activity; Dimorphandra mollis; Flavonoids